The facilitators of and barriers to antimicrobial use and misuse in Lalitpur, Nepal: a qualitative study - Summita Udas; Obindra Bahadur Chand; Babin Shrestha; Sushmita Pathak; Sarita Syantang; Ashata Dahal; Abhilasha Karkey; Abhishek Giri; Olita Shilpakar; Buddha Basnyat; Olawale Salami; Juvenal Nkeramahame; et al. (BMC, 2024)
Abstract Background Antimicrobial resistance (AMR) is a pressing global health concern driven by inappropriate antibiotic use, which is in turn influenced by various social, systemic, and individual factors. This study, nested within FIND's AMR Diagnostic Use Accelerator clinical trial in Nepal, aimed to (i) explore the perspectives of patients, caregivers, and healthcare workers (HCWs) on antibiotic prescription adherence and (ii) assess the impact of a training and communication (T&C) intervention on adherence to antibiotic prescriptions. Methods Using qualitative, semi-structured interviews, pre-intervention and Day 7 follow-up components, and the Behaviour Change Wheel process, we investigated the facilitators of and barriers to the use and misuse of antibiotic prescriptions. Results Results of the study revealed that adherence to antibiotic prescriptions is influenced by a complex interplay of factors, including knowledge and understanding, forgetfulness, effective communication, expectations, beliefs and habits, attitudes and behaviours, convenience of purchasing, trust in medical effectiveness, and issues of child preferences. The T&C package was also shown to play a role in addressing specific barriers to treatment adherence. Conclusions Overall, the results of this study provide a nuanced understanding of the challenges associated with antibiotic use and suggest that tailored interventions, informed by behaviour frameworks, can enhance prescription adherence, may be applicable in diverse settings and can contribute to the global effort to mitigate the rising threat of AMR.